British sharks in Sicily: records of long distance migration of tope shark (Galeorhinus galeus) from North-eastern Atlantic to Mediterranean Sea. - COLLOCA, FRANCESCO; SCANNELLA, DANILO; GERACI, MICHELE LUCA; FALSONE, FABIO; BATISTA, GIUSTO; VITALE, SERGIO; DI LORENZO, MANFREDI; ΒΟΝΟ, GIOACCHINO (Mediterranean Marine Science, 2019)
The study reports information about the recapture of two tagged adult females of tope shark, Galeorhinus galeus (Linnaeus 1758), in the central Mediterranean Sea (south coasts of Sicily) in 2014 and 2017. The two females were tagged in North-East Atlantic, respectively in Scotland in 2009 and Ireland in 2015. The Scottish specimen was a 175 cm female increasing of about 10 kg in body weight and 37 cm in total length during its 1967 days at liberty (5.39 years). The Irish one, was a pregnant female of an estimated age of 15-17 year which spent 248 days at liberty increasing 14 cm during this period. The growth rate of the two specimens was therefore between 6.8 and 7.8 cm year-1, faster than the annual increments of adults suggested in previous studies. Previous tope recapture records in the Mediterranean Sea were limited to the Alboran Sea, coast of Valencia and the Algerian coasts. The two tope females recaptured in the Strait of Sicily provided the first evidence of long distance entrance of NE Atlantic tope in the Mediterranean Sea. The well known occurrence of mature females and juveniles in this area of the Mediterranean suggest the hypothesis of a migration of adults female from their feeding grounds in north eastern Atlantic to lower latitudes up to the Mediterranean Sea for parturition.